UPAYA PEMBENTUKAN KARAKTER SISWA MELALUI PENANAMAN NILAI RELIGIUS DALAM KULTUR SEKOLAH DI SDN 3 SUKAMULIA TIMUR - nurfaridah, fathin; Parhanuddin, lalu; mukti, husnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate: (1) the process of character building implemented at SD Negeri 3 Sukamulia Timur, (2) the development of students’ character through the internalization of religious values, and (3) the supporting and inhibiting factors in the process of character building. This research employs a qualitative approach with the principal, homeroom teachers, Islamic education teachers, and several sixth-grade students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings reveal that: (1) the process of students’ character building at SD Negeri 3 Sukamulia Timur is carried out in a structured and consistent manner through habituation activities based on religious values that are integrated into the school culture, supported by extracurricular activities designed to strengthen positive values in shaping students’ character; (2) the internalization of religious values covers aspects of faith, worship, and morality, implemented through role modeling and habituation methods, such as the recitation of Asmaul Husna, short verses, daily prayers, congregational prayer, imtaq and almsgiving, the 5S principle, and Islamic commemoration events (PHBI); (3) supporting factors include a conducive environment, consistent positive habituation, and effective communication and collaboration between school and parents. Conversely, inhibiting factors include students’ limited understanding of religious values, lack of intrinsic motivation, inadequate facilities and infrastructure, digital distractions, as well as unsupportive family and social backgrounds.